2001
DOI: 10.1590/s1516-31802001000100004
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of caustic substances and its complications

Abstract: The complications were related to the amount of caustic soda ingested. Small amounts caused esophagitis or stenosis and large amounts increased the risk of fistulas, perforations and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
18

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 14 publications
3
81
0
18
Order By: Relevance
“…A pH value higher than 12 increases the possibility of injury, because the critical cut-off pH for esophageal ulceration is 12.5 (4). Previous work has shown that 3.8% NaOH causes mucosalsubmucosal esophageal burn, 10.7% NaOH causes muscular layer injury, and 22.5% NaOH causes full-thickness injury (1,5). In the present study, all of the bleaches had a pH value higher than 12, and 4 were above 12.5.…”
Section: Labelsupporting
confidence: 51%
“…A pH value higher than 12 increases the possibility of injury, because the critical cut-off pH for esophageal ulceration is 12.5 (4). Previous work has shown that 3.8% NaOH causes mucosalsubmucosal esophageal burn, 10.7% NaOH causes muscular layer injury, and 22.5% NaOH causes full-thickness injury (1,5). In the present study, all of the bleaches had a pH value higher than 12, and 4 were above 12.5.…”
Section: Labelsupporting
confidence: 51%
“…Caustic substances cause tissue destruction through liquefaction or coagulation reactions and the intensity of destruction depends on the type, concentration, time of contact and amount of the substance ingested. [1] Alkali ingestion is much more devastating and almost always Leads to significant destruction of tissue, resulting in long-term dysfunction. Alkali ingestion causes liquefactive injury [2] and deep penetration of tissue.…”
Section: Pathological Discussionmentioning
confidence: 99%
“…Caustic substances cause tissue destruction through liquefaction or coagulation reaction and the intensity of destruction depends on type, concentration, time of contact [1] and amount of the substance ingested [3]. Our patient held a liquid in her mouth but spit it out without swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a majority of the published literature relating to caustic ingestion are concerned with return of function of the strictured esophagus and stomach [1][2][3].…”
Section: Introductionmentioning
confidence: 99%